Determination of Mercury in Fly Ash by Flameless Cold Vapour Atomic Absorption Spectrometry Using Hydride Generator - Singh, Nahar; Sarkar, A.K. (Asian Journal of Chemistry, 2010)
An accurate, reliable and sensitive method has been developed for the determination of mercury in fly ash. Hydrofluoric acid reacts with fly ash and releases mercury, which is converted into non-volatile form by reacting with nitric acid and perchloric acid. The elemental mercury formed after reduction with sodium borohydride (NaBH4) is determined by flameless atomic absorption spectrometry using hydride generator. The fly ash sample analyzed was received from National Council for Cement and Building Materials (NCCBM), which will be used as reference material in future. The validity of the method has been established by comparing the results obtained from NIST certified reference material 1633(b). The standard deviation has been calculated by analyzing ten replicates of both fly ash samples.